Effect of Nd:YAG, Er, Cr:YSGG Laser Irradiation, and Adjunctive Photodynamic Therapy on Push-Out Bond Strength of Zirconia Posts to Radicular Dentin. (6th May 2021) - Alshammary, Freah; Karobari, Mohmed I.; Assiry, Ali A.; Marya, Anand; Shaikh, Gul M.; Siddiqui, Ammar A.; Alam, Mohammad K.
Abstract : This study is aimed at assessing the influence of Nd:YAG, Er, Cr:YSGG laser irradiation, and adjunctive photodynamic therapy (aPDT) on the bond strength of zirconia posts to radicular dentin. Eighty extracted anterior teeth were randomly categorized into 4 groups (n = 20 ) based on varying laser irradiation treatments, i.e., conventional cleaning and shaping (CCS), Nd:YAG, Er, Cr:YSGG, and aPDT group, respectively. Using a cutting machine, the samples were prepared for push-out bond strength analysis; 4 sections (2 on each apical and cervical) of around 1 mm thickness were sectioned for all roots at a right angle to the long axis of the post. After making the space for the post, they were incorporated into the root system and were subjected to different laser treatments. The universal testing machine was utilized to assess the push-out bond strength, which had a defined 1 mm/minute crosshead speed until the failure was encountered. Specimens in the aPDT group (8.20 ± 2.14  MPa) demonstrated the highest mean push-out bond strength, whereas the lowest was shown by samples in the CCS group (7.08 ± 1.11  MPa). According to the independent t -test, the mean push-out bond strength scores of the cervical segments were higher as compared to the apical segments in research groups (p < 0.05 ). Overall, the adhesive type was the most frequently encountered failure mode in all of the experimental groups, with the least number of failures observed in aPDT treated teeth samples. In conclusion, the push-out bond strength to radicular dentin was not much influenced by Nd:YAG, Er, Cr:YSGG laser, and aPDT in comparison with CCS. Although statistically not significant, however, the application of aPDT provided better outcomes as compared to other research groups.